The Effect of Paid Parental Leave on Child Health in Australia - Barbara Broadway; Guyonne Kalb; Daniel Kuehnle; Miriam Maeder (Institute for the Study of Labor (IZA), 2015)
Providing mothers with access to paid parental leave may be an important public policy to improve child and maternal health. Using extensive information from the Australian Longitudinal Study of Children (LSAC), we contribute to the literature by estimating the effect of paid parental leave entitlements on child health up to age seven. Exploiting detailed information on children's health, family background, mothers' pre-birth work histories and mothers' health behaviours during pregnancy within a propensity score matching framework, we show that paid parental leave entitlements reduce the probability of a child having multiple ongoing health conditions, but do not significantly affect any single condition. We find that the effect on multiple conditions is strongest for children from lower socio-economic backgrounds. Our study implies that the provision of paid parental leave, even for short periods (as usually available in Australia), will benefit children's health.
Keywords: I1; 330; child health; parental leave; Australia; LSAC